THE USE OF “THERE IS” AND “THERE ARE” IN ENGLISH GRAMMAR: A SCIENTIFIC PERSPECTIVE - Quvvatova Zebuniso Zohirovna; Makhanova Mukhayyo Nabiyevna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract This article examines the grammatical constructions ’there is’ and ’there are,’ which serve as existential structures in English. These forms introduce the existence or presence of a subject and are essential for conveying spatial and temporal information. The discussion encompasses their syntactic and semantic roles, common usage patterns, and pedagogical implications in English language teaching. Special emphasis is placed on the challenges these structures pose for non-native learners and strategies to enhance comprehension and usage in academic and conversational contexts.